2008
DOI: 10.1029/2008gl034158
|View full text |Cite
|
Sign up to set email alerts
|

A global climatology of ionospheric irregularities derived from GPS radio occultation

Abstract: [1] GPS radio occultation measurements from CHAMP, GRACE-A and FORMOSAT-3/COSMIC are used to derive global information on small-scale ionospheric irregularities such as sporadic E layers between January 2002 and December 2007. The investigations are based on the analysis of amplitude variations of the GPS radio occultation signals. The global distribution of ionospheric irregularities shows strong seasonal variations with highest occurrence rates during summer in the middle latitudes. The long-term data set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
268
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(325 citation statements)
references
References 22 publications
54
268
3
Order By: Relevance
“…Fig ure 17 shows initial re sults of these in ves ti ga tions and dem on strates that the avail abil ity of the FORMOSAT-3/COS MIC data al lows the char ac ter iza tion of the global dis tri bu tion with un prec edented res o lu tion in time and space (Ar ras et al 2008). With an oc cur rence fre quency of up to around 50% of all occultations in par tic u lar re gions, spo radic E is a sig nif i cant phe nom e non in the lower ion o sphere.…”
Section: Global In Ves Ti Ga Tions Of Ion O Spheric Ir Reg U Lar I Tiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig ure 17 shows initial re sults of these in ves ti ga tions and dem on strates that the avail abil ity of the FORMOSAT-3/COS MIC data al lows the char ac ter iza tion of the global dis tri bu tion with un prec edented res o lu tion in time and space (Ar ras et al 2008). With an oc cur rence fre quency of up to around 50% of all occultations in par tic u lar re gions, spo radic E is a sig nif i cant phe nom e non in the lower ion o sphere.…”
Section: Global In Ves Ti Ga Tions Of Ion O Spheric Ir Reg U Lar I Tiesmentioning
confidence: 99%
“…We de rived the lo ca tion of the spo radic E-lay ers us ing am pli tude vari a tions of the RO sig nal as an in di ca tor (Wickert et al 2004b, Ar ras et al 2008) . Fig ure 17 shows initial re sults of these in ves ti ga tions and dem on strates that the avail abil ity of the FORMOSAT-3/COS MIC data al lows the char ac ter iza tion of the global dis tri bu tion with un prec edented res o lu tion in time and space (Ar ras et al 2008).…”
Section: Global In Ves Ti Ga Tions Of Ion O Spheric Ir Reg U Lar I Tiesmentioning
confidence: 99%
“…Therefore it is not possible to observe sporadic E layers at higher altitudes where its formation might be influenced by the meridional wind or the descending intermediate layers. A more detailed description and initial results of the application of this technique are given by Arras et al (2008) and Wickert et al (2009).…”
Section: Measurements and Data Analysismentioning
confidence: 99%
“…L-band scintillations and their relations with plasma irregularities at both ionospheric E-(e.g., Hocke et al, 2001;Arras et al, 2008) and F-regions (e.g., Brahmanandam et al, 2012;Dymond et al, 2012;Carter et al, 2013). Buchert et al (2015) reported that the GPS receiver onboard Swarm satellites repeatedly encountered signal interruptions during January and February 2014.…”
Section: Introductionmentioning
confidence: 99%